Islam, Media and Social Responsibility in the Muslim World - Ratnayuningsih, Yeni (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
In recent years, the internet and social media have played a great role in the society. This has been indicated by, among others, how popular culture in the film and media industry has influenced youth culture, including those in the Muslim world. Meanwhile, certain images of Islam might have changed overtime but the discourse about the Muslim world might have also been shaped and reshaped by the media and the powerful media industry behind it. So, how should the Muslim world respond to this? Should the media be responsible for this change? If the Muslim world, as perhaps many others, has concerns about the way the media shapes our world and our way of perceiving things, what is the best solution to communicate these concerns and convey these messages to the wider audience?DOI: 10.15408/sdi.v20i3.517